1995
DOI: 10.1002/hep.1840210316
|View full text |Cite
|
Sign up to set email alerts
|

Macroregenerative nodules in a series of adult cirrhotic liver explants: Issues of classification and nomenclature

Abstract: Macroregenerative nodules (MRNs), probably representing a pathway for human hepatocarcinogenesis, are generally classified into type I MRNs (or ordinary adenomatous hyperplasia) and type II MRNs (or atypical adenomatous hyperplasia), on the basis of imprecise definitions of cytological and architectural atypia. It is currently believed that type II MRNs are probably true precursors of hepatocellular carcinoma (HCC), whereas type I lesions may simply represent large regenerative nodules. A series of 155 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 23 publications
5
94
2
1
Order By: Relevance
“…28,29 Indeed, recent studies have accumulated evidence suggesting that LLCC in cirrhotic liver is merely a diffuse and degenerative change to prolonged cholestasis, rather than a neoplastic feature. 4,6,30,31,32 The question arises as to whether there exists several subsets of LLCC, with a benign form of scattered LLCC associated with prolonged cholestasis and a neoplastic subset consisting of clusters of large liver cells in cirrhotic macronodules. In our study, none of the cases with LLCC showed any association with bile or cholate stasis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Indeed, recent studies have accumulated evidence suggesting that LLCC in cirrhotic liver is merely a diffuse and degenerative change to prolonged cholestasis, rather than a neoplastic feature. 4,6,30,31,32 The question arises as to whether there exists several subsets of LLCC, with a benign form of scattered LLCC associated with prolonged cholestasis and a neoplastic subset consisting of clusters of large liver cells in cirrhotic macronodules. In our study, none of the cases with LLCC showed any association with bile or cholate stasis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 These macronodules are common findings in cirrhosis and are often related to viral infection (hepatitis C and B virus), with a prevalence ranging from 10% to 42% in cirrhotic explanted livers. [2][3][4][5][6] Interestingly, recent advances in imaging modalities have led to the detection of these large nodular lesions in follow-up of cirrhotic patients. 7 Different types of macronodules can be distinguished according to their imaging and pathological characteristics, and several classifications have already been established.…”
mentioning
confidence: 99%
“…1 Although HGDNs are characterized by a number of cytoarchitectural abnormalities, [1][2][3][4][5][6] there are still difficulties in making the morphological distinction between LRNs (which are thought to be a simple hyperplastic growth) and LGDNs (which are thought to be a putative premalignant growth). Indeed, the former are lesions cytoarchitecturally similar to the adjacent cirrhotic parenchyma whereas LGDNs are characterized by mild atypias usually, but not necessarily, under the form of large cell changes.…”
mentioning
confidence: 99%
“…LRNs typically take place in a cirrhotic setting and outnumber the so-called dysplastic nodules as detected in vivo by ultrasound 8 or after anatomic dissection. [2][3][4][5][6] Thus, the assessment of the arterial and capillary profile of LRNs can provide diagnostic information and clues as well as validate them as hyperplastic rather than dysplastic growths. 7,9-11 Indeed, most nonneoplastic-sizable nodules arising in cirrhosis are notoriously quite similar by image analysis, 8,[12][13][14] macroscopically, and, to some extent, also microscopically.…”
mentioning
confidence: 99%
“…Any of these can make biopsy diagnosis difficult. Other than true dysplastic nodules [19,20], very well differentiated HCCs, large regenerative nodules [19][20][21][22][23] with high cellularity, mixture of HCC cells and benign cells, well-differentiated HCCs with marked fatty change, benign large regenerative nodules with marked fatty change, thick sliced specimens with high cellularity and strong stainability of cytoplasm, and FNH with high cellularity and microacinar formation can be arbitrarily diagnosed as dysplastic nodules despite not being true dysplastic nodules. Or the result can be a false-negative or a false-positive diagnosis.…”
Section: Histological Diagnosis Of Early Hccs Of Biopsied Specimensmentioning
confidence: 99%